The Relationship between Learning Orientation and the Performance of Small and Medium Enterprises in South Africa - Evelyn Motsepe; Olawale Fatoki (Journal of Economics and Behavioral Studies, 2017)
Small and medium enterprises (SMEs) are an important vehicle in income re-distribution, poverty alleviation, employment creation and contribute to the gross domestic product of South Africa. However, SMEs in South Africa suffer from a weak level of performance and a high failure rate. The main objective of this study was to investigate the impact of learning orientation on the performance of SMEs. A quantitative approach was used, while a self-administered questionnaire was also employed during data collection process. A three- section questionnaire covering demographic information, learning orientation variables and performance variables was prepared and distributed randomly to a selected sample of 390 SME owners in Msukaligwa Local Municipality in Mpumalanga Province of South Africa. A total of 181 questionnaires were returned. Descriptive statistics, factor analysis, correlation and regression analysis were used for data analysis. The Cronbach’s alpha was used to measure reliability. The results of the study revealed a significant positive relationship between learning orientation and the performance of SMEs. Recommendations to improve the learning orientation of SMEs are suggested.